1)
2)
3) По условию
получаем уравнение:
По условию
и , значит,
получаем
4) А теперь находим дискриминант квадратного трехчлена .
Ответ: 17
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1)![f(c)=ac^2-5c+c=ac^2-4c f(c)=ac^2-5c+c=ac^2-4c](https://tex.z-dn.net/?f=f%28c%29%3Dac%5E2-5c%2Bc%3Dac%5E2-4c)
2)![f(2c)=a(2c)^2-5*2c+c=4ac^2-10c+c=4ac^2-9c f(2c)=a(2c)^2-5*2c+c=4ac^2-10c+c=4ac^2-9c](https://tex.z-dn.net/?f=f%282c%29%3Da%282c%29%5E2-5%2A2c%2Bc%3D4ac%5E2-10c%2Bc%3D4ac%5E2-9c)
3) По условию![f(c)=2f(2c) f(c)=2f(2c)](https://tex.z-dn.net/?f=f%28c%29%3D2f%282c%29)
получаем уравнение:
По условию![c\neq 0 c\neq 0](https://tex.z-dn.net/?f=c%5Cneq%200)
и
, значит,
получаем![ac=2 ac=2](https://tex.z-dn.net/?f=ac%3D2)
4) А теперь находим дискриминант квадратного трехчлена
.
Ответ: 17